Association between Asthma and Periodontitis - Sung Joon Park; Hahn Jin Jung; Min Woo Park; Hyo Geun Choi; Heejin Kim; Jee Hye Wee (Diagnostics, 2023)
The current study aimed to investigate the association between asthma and periodontitis in the Korean adult population. Data from the Korean Genome and Epidemiology Study Health Examinees between 2004 and 2016 were considered. Of the 173,209 participants, 2521 asthmatic and 132,806 control participants were selected. The participants were categorized according to their current status of asthma, as ‘well-controlled’, ‘being treated’, and ‘not being treated’. The prevalence of periodontitis was found to be significantly higher in the participants with asthma (13.1%) than in the controls (7.3%). In the fully adjusted model, the patients with asthma had a higher odds ratio (OR = 1.79, 95% confidence interval [CI] = 1.59–2.02, p < 0.001) for periodontitis than those without asthma. The results were consistent across all the age and sex subgroups. The adjusted ORs for periodontitis were 2.15 (95% CI = 1.68–2.76, p < 0.001) in the ‘well-controlled’ asthma group, 1.44 (95% CI = 1.16–1.78, p < 0.001) in the ‘being treated’ asthma group, and 1.86 (95% CI = 1.55–2.22, p < 0.001) in the ’not being treated’ asthma group compared to the control group. Overall, we found asthma to be associated with periodontitis in Korean adults, and the participants with well-controlled asthma had the highest ORs for periodontitis.